PENGARUH KEPUASAN PELANGGAN, LOYALITAS PELANGGAN DAN KUALITAS PELAYANAN TERHADAP CITRA PERUSAHAAN PADA PT. RITRA CARGO INDONESIA CABANG SEMARANG - Yudho Purnomo; Sugiarto (E-logis : Jurnal Ekonomi Logistik, 2021)
The company's benchmark for meeting all consumer needs is customer satisfaction. Companies capable of delivering good service can produce trust and loyalty from each customer in order to re-purchase goods or reuse services used by consumers. With the support of complete facilities, the quality of service provided by the company to customers will also be better. In the eyes of clients, this would also create a positive image. This study aims to determine the effect of customer satisfaction, customer loyalty and service quality on corporate image at PT. Ritra Cargo Indonesia Semarang Branch. The analysis technique in this research is to use quantitative analysis methods based on a statistical approach. The population used in this study were customers of PT. Ritra Cargo Indonesia Semarang Branch with a sample of 80 respondents. The results of this test indicate the influence of customer satisfaction, customer loyaltyand customer quality, customer loyalty and customer quality, each of which has a positive and significant effect on the corporate image of PT. Ritra Cargo Indonesia Semarang Branch.